Spironolactone and Dimethylsulfoxide Effect on Glucose Metabolism and Oxidative Stress Markers in Polycystic Ovarian Syndrome Rat Model - Dăneasă, A.; Cucolaș, C.; Furcea, M.; Bolfa, P.; Dudea, S.; Olteanu, D.; Alupei, M. C.; Mureșan, A.; Filip, G. A. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Because polycystic ovarian syndrome (PCOS) is a risk factor for type 2 diabetes, the affected women can present frequently prediabetic states such as impaired fasting glycaemia and/or impaired glucose tolerance. The purpose of our study is to explore the effect of antiandrogenic spironolactone on glucose metabolism and oxidative stress (OS) parameters in oestradiol valerate (OV) induced PCOS rat model.72 female Wistar rats were distributed either to PCOS group (n=65, OV dissolved in sesame oil, 5 mg/0.4 ml), or to non-PCOS control group (n=7, sesame oil, 0.4 ml). After a month, ultrasound was performed to assess the ovarian morphology, and the results of an initial oral glucose tolerance test (OGTT) were used to identify the animals with altered glucose metabolism (AGM). Glucose transporter 4 (GLUT4) was evaluated from muscle biopsies, OS parameters were assessed from blood and muscle samples, and ovaries of 3 rats were removed for histopathological examination. Afterwards, the AGM group was divided in a treated PCOS group denoted as Sp+D (per os spironolactone dissolved in DMSO, 2 mg/0.2 ml), and a PCOS control treated with DMSO (0.2 ml). After one month of daily treatment, a final OGTT was performed. GLUT4 and OS parameters were again evaluated and ovaries were removed for histopathological examination.As compared to the values prior to the treatment, Sp+D reversed fasting hyperglycaemia (p<0.001), increased GLUT4 immunoreactivity in the perinuclear compartment (p<0.05) and translocation to plasmalemma (p<0.001) and improved superoxide dismutase (0.001<p<0.01) and glutathione peroxidase (0.001<p<0.01) activities, while reducing GSH level (0.001<p<0.01). Administration of DMSO alone decreased fasting hyperglycaemia (p<0.001) and 2-h glucose level (p<0.05) independently of GLUT4 translocation, improved superoxide dismutase (p<0.001) and glutathione peroxidase (p<0.05) activities in erythrocytes, reduced GSH level in serum (p<0.05) and diminished lipid peroxidation in muscle as compared to the values recorded before treatment (0.001<p<0.01).Our results showed that the Sp+D treatment improved antioxidant capacity and had a beneficial effect on metabolic deregulation in PCOS. Administration of DMSO had an unexpected hypoglycaemiant effect and improved OS parameters. This may represent an indirect proof of the role of oxidative stress and inflammation in PCOS and glucose metabolism abnormalities encountered in PCOS.
Keywords: polycystic ovarian syndrome; fasting hyperglycaemia; glucose transporter 4; oxidative stress; spironolactone; dimethylsulfoxide